Validity of a food-frequency questionnaire for elderly men in southeast China - Jian, Le; Binns, Colin; Lee, Andy (Cambridge University Press, 2006)
OBJECTIVE: To investigate the internal validity of a food-frequency questionnaire (FFQ) developed for a case-control study of prostate cancer in southeast China. DESIGN: A comprehensive questionnaire comprising a quantitative FFQ and a short food habit questionnaire (SFHQ) was developed and modified from previous cancer and nutritional studies. The Goldberg formula (ratio of energy intake (EI) to basal metabolic rate (BMR), EI/BMR) was used to assess the validity of the FFQ by making comparisons with physical activity levels. Physical activity levels were measured by the estimated total metabolic equivalents (MET) and the ratio of energy expenditure (EE) to BMR (EE/BMR). Correlation analyses were undertaken to compare the SFHQ variables with those of the quantitative FFQ. SETTING: Hangzhou, Zhejiang Province, China. SUBJECTS: A total of 404 men over 45 years old with or without prostate cancer were recruited from eight hospitals.RESULTS: The partial correlation coefficients, controlling for age and family history of prostate cancer, were moderate to high (P<0.05) for preserved foods intake, fat consumption and tea drinking variables between the SFHQ and the quantitative FFQ. The average EI/BMR was 1.72, with 76% of subjects exceeding the Goldberg cut-off value of 1.35. Apart from weight, BMI, EE/BMR and MET, there were no significant differences in characteristics between low (<1.35) and normal EI/BMR groups. CONCLUSIONS: The FFQ is demonstrated to be a valid instrument to measure energy and food intake for elderly men in southeast China.